Extraction of essential oils from patchouli leaves using ultrasonic - assisted solvent extraction method - Muhd Zahiruddin, Shukor (2008)
Essential oil is an aromatic liquid that is extracted from various parts of the plants. It contains the true essence of the plant and has many therapeutic benefits. Patchouli essential oil from the extraction of dried Patchouli (Pogostemon Cablin) leaves is the important ingredient in many fragrance products like perfumes and also use widely in medical field. This experiment use ultrasonication-assisted solvent extraction method that comprises two set of experiments in order to investigate the effect of ultrasonic and type of solvent on extraction process. Ethanol, hexane and acetone are the solvents used for the first experiment. The best solvent among three is chosen to be used in second experiment. In the second experiment, ultrasound is used in order to investigate its effect compared to the experiment without using ultrasonic. The qualitative and quantitative analysis has been done in order to show the objectives were achieved. Qualitative analysis involved the chromatogram analysis from GCMS while quantitative analysis is based on the percent yield. From qualitative analysis, ethanol gives the highest peak area (27.92%) than hexane (20.01%) and acetone (20.42%). In addition, average peak area for ultrasonic method (50.18%) is better than without using ultrasonic (42.40%). Meanwhile, for qualitative analysis, ethanol can extract highest yield (2.87%) compared to hexane (2.53%) and acetone (2.00%). Then, by using ultrasonic, it gives higher average yield (2.27%) than without using ultrasonic (1.67%). Therefore, from these analyses, the best solvent used for solvent extraction is ethanol because it produced highest quality and most yields of patchouli oil. This experiment also has the better result when it involves the ultrasonication method.